JUAL TANAH BERDASARKAN DOKUMEN SERTIFIKAT TANAH - Ridho Harry Setiawan; Hanafi Tanawijaya (Fakultas Hukum Universitas Tarumanagara, 2022)
Land is one of the valuable assets whose existence can be used as long-term assets, long-terminvestments and can be used as assets that can be inherited properly as long as the land has legalland rights according to the applicable laws and regulations. Land is also the most basic source ofhuman livelihood, for example, to build a place to live or to be used as a source of livelihood. Thisis in line with the fact that humans live and develop and carry out activities on land so thatwhenever humans come into contact with land, in this case humans are also accustomed to buyingand selling land and doing so without having a letter. which do not have a strong legal basis sothat problems occur. How is legal protection for land rights holders with land certificatedocuments? The research method used is normative juridical with a case approach and legislationbased on analytical studies that legal protection must be obtained by all legal subjects without anydif erences.